Conference Essay: The Relationship between Gender Studies and Discourse Studies: Synergies, Frictions, and Pitfalls - Kleiner, Bettina; Dinsleder, Cornelia (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2017)
The interdisciplinary conference "Gender Studies Meets Discourse Studies Meets Gender Studies: Entanglements, Affinities, Tensions, and Open Questions" focused on the relationship between gender studies and discourse studies. On the one hand this essay provides insights into the conference debates, and on the other it critically discusses the contributions. The following three key aspects provide guidelines for reconstructing and developing the arguments: 1. theoretical perspectives on the relation of discourse/power/subject to gender and sexuality; 2. discourse analysis focusing on gender and sexuality in written (media) texts; and 3. empirical research informed by discourse studies and gender studies—analysis of interviews, documents, focus groups, and YouTube videos. Retrospectively discussing and elaborating the conference contributions, we will particularly pay attention to the question of how discourse and gender were conceptualized and interrelated. Subsequently, we critically reflect upon objects of investigation and their implied approaches. Finally, we consider the outcomes of the conference and future prospects. Overall, the essay aims at outlining the potential of a consistent combination of gender studies and discourse studies.